2017
DOI: 10.13073/fpj-d-17-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cradle-to-Gate Life-Cycle Impact Analysis of Glued-Laminated (Glulam) Timber: Environmental Impacts from Glulam Produced in the US Pacific Northwest and Southeast*

Abstract: This study was an update on the 2000 life-cycle inventory data on material and energy inputs associated with the production of 1 m3 of glued-laminated (glulam) timbers produced in the Pacific Northwest (PNW) and the Southeast (SE) regions of the United States. This article looks at the cradle to gate for the entire glulam production processes, which include forest harvest, lamstock production, and glulam beam production. Data collected from glulam beam manufacturers in 2013 allowed for the development of a lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…255 As displayed in Figure 20B, Bowers et al performed a cradle-to-gate LCA on glulam and showed the contribution of each life cycle stage (i.e., forest operation, lamstock production, and glulam production) to six environmental impact categories. 212 The results indicate that GWP and ozone depletion are mostly driven by glulam production, while eutrophication and smog formation are nearly equally contributed by all three life cycle stages. Bergman and Alanya-Rosenbaum studied the lifecycle environmental impacts of I-joist produced in the Pacific Northwest (PNW) and Southeast (SE) U.S., their system contained five life-cycle stages, namely forest operations, LVL production, finger-jointed lumber production, OSB production, and I-joist production.…”
Section: Lcas Of Traditional Engineered Wood Productsmentioning
confidence: 92%
See 1 more Smart Citation
“…255 As displayed in Figure 20B, Bowers et al performed a cradle-to-gate LCA on glulam and showed the contribution of each life cycle stage (i.e., forest operation, lamstock production, and glulam production) to six environmental impact categories. 212 The results indicate that GWP and ozone depletion are mostly driven by glulam production, while eutrophication and smog formation are nearly equally contributed by all three life cycle stages. Bergman and Alanya-Rosenbaum studied the lifecycle environmental impacts of I-joist produced in the Pacific Northwest (PNW) and Southeast (SE) U.S., their system contained five life-cycle stages, namely forest operations, LVL production, finger-jointed lumber production, OSB production, and I-joist production.…”
Section: Lcas Of Traditional Engineered Wood Productsmentioning
confidence: 92%
“…These contributors can be either life cycle stages (e.g., forest operations, panel production, use phase) or processes (e.g., chipping, heat generation, resin application, sawing) . As displayed in Figure B, Bowers et al performed a cradle-to-gate LCA on glulam and showed the contribution of each life cycle stage (i.e., forest operation, lamstock production, and glulam production) to six environmental impact categories . The results indicate that GWP and ozone depletion are mostly driven by glulam production, while eutrophication and smog formation are nearly equally contributed by all three life cycle stages.…”
Section: Lca Of Engineered Wood Productsmentioning
confidence: 99%
“…However, no studies have yet compared the environmental impacts of MT buildings and conventional buildings for different building heights and across different United States (U.S.) regions. Cradle-to-gate product LCAs indicated net negative carbon emissions for MT products, which positions them with a high environmental advantage over nonwood materials [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Inventory data on forestry operations and transportationthat part of the product life cycle upstream from the TM facilityare available in other work for those wishing to extend the gate-to-gate accounting presented here. See, for example, ref for an international survey and ref for US Pacific Northwest operations as well as the U.S. Life Cycle Inventory Database . A series of reports and papers from the Consortium for Research on Renewable Industrial Materials (CORRIM) includes both forestry operations and softwood lumber production in the inland northwest region, where the TM facility studied here is located.…”
Section: Methodsmentioning
confidence: 99%